DETERMINATION OF OIL DRAIN PERIOD IN NAVAL SHIP DIESEL ENGINE - Kaleli, H.; Yildirim, E. (SCIBULCOM LTD, 2009)
The performance requirement of lubricating oils is rising continuously in terms of oil drain intervals, reduced friction and wear of the components in internal combustion engines. The oil drain capability of the engines must be considered to properly estimate oil drain intervals for the equipment in economic point of view. The primary goal of this research is to determine the useful lifetime of the lubrication oil in the diesel engine. Firstly, the chemical and physical analysis of used mineral crankcase oil is studied to predict the condition of the lubricant and engine wear components during continuous operation by using analysis methods and techniques. Secondly, the optimum oil drain period is determined according to the calculations of cost analysis and iron wear element concentration value during engine overhaul period results of oil sample analysis. Examined oil samples were taken from a ship main diesel engine belonging to the naval forces in Turkey. Lubricant samples were examined approximately every 40 h for deterioration of the lubricant and evidence of wear of the engine components. Finally, the optimum oil drain interval for the mineral SAE 30 oil is found as 775 h in this experimental study. As the oil drain interval is 300 operating h instead of 775 operating h, the extra cost paid for the lubricant is 3357.49 euro. In case that there is an average of two oil changes per year for one ship, this cost increases to 6714.98 euro for one ship.
Keywords: marine ship diesel engines; oil analysis; optimum oil drain period; economic analysis; Engineering